Choice of Nonionic Surfactant Used to Formulate Type IIIA Self‐Emulsifying Drug Delivery Systems and the Physicochemical Properties of the Drug Have a Pronounced Influence on the Degree of Drug Supersaturation that Develops During In Vitro Digestion. Issue 4 (27th January 2014) - Devraj, Ravi; Williams, Hywel D.; Warren, Dallas B.; Porter, Christopher J. H.; Pouton, Colin W.
<x xml:space="preserve">Abstract</x> The performance of self‐emulsifying drug delivery systems (SEDDS) is influenced by their tendency to generate supersaturated systems during dispersion and digestion in the gastrointestinal tract. This study investigated the effect of drug loading on supersaturation during digestion of fenofibrate or danazol SEDDS, each formulated using long‐chain lipids and a range of nonionic surfactants. Supersaturation was described by the maximum supersaturation ratio (SRM) produced by in vitro digestion. This parameter was calculated as the ratio of the total concentration of drug present in the digestion vessel versus the drug solubility in the colloidal phases formed by digestion of the SEDDS. SRM proved to be a remarkable indicator of performance across a range of lipid‐based formulations. SEDDS containing danazol showed little evidence of precipitation on digestion, even at drug loads approaching saturation in the formulation. In contrast, fenofibrate crystallized extensively on digestion of the corresponding series of SEDDS, depending on the drug loading. The difference was explained by the generation of higher SRM values by fenofibrate formulations. A threshold SRM of 2.5–2.6 was identified in six of the seven SEDDS. This is not a definitive threshold for precipitation, but in general when SRM is greater than 3, fenofibrate supersaturation could not be maintained. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:1050–1063, 2014